2013
DOI: 10.1109/tip.2013.2271192
|View full text |Cite
|
Sign up to set email alerts
|

Shortest-Path Constraints for 3D Multiobject Semiautomatic Segmentation Via Clustering and Graph Cut

Abstract: To cite this version:Razmig Kéchichian, Sébastien Valette, Michel Desvignes, Rémy Prost. Shortest-path constraints for 3D multiobject semiautomatic segmentation via clustering and Graph Cut. IEEE Transactions on Image Processing, Institute of Electrical and Electronics Engineers, 2013, 22 (11) Abstract-We derive shortest-path constraints from graph models of structure adjacency relations and introduce them in a joint centroidal Voronoi image clustering and Graph Cut multiobject semiautomatic segmentation frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Therefore, we simplify the image prior to segmentation by an image-adaptive centroidal Voronoi tessellation (CVT), which strikes a good balance between cluster compactness and object boundary adherence and helps to place subsequent segmentation boundaries precisely. We have shown that the clustering step improves the overall run-time and memory footprint of the segmentation process up to an order of magnitude without compromising the quality of the result [14].…”
Section: Image Clusteringmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we simplify the image prior to segmentation by an image-adaptive centroidal Voronoi tessellation (CVT), which strikes a good balance between cluster compactness and object boundary adherence and helps to place subsequent segmentation boundaries precisely. We have shown that the clustering step improves the overall run-time and memory footprint of the segmentation process up to an order of magnitude without compromising the quality of the result [14].…”
Section: Image Clusteringmentioning
confidence: 99%
“…11.3 encode prior information on interactions between labels assigned to pairs of neighbouring variables encouraging the spatial consistency of labelling with respect to a reference model. We define these terms according to the piecewise-constant vicinity prior model proposed in [14], which, unlike the standard Potts model, incurs multiple levels of penalization capturing the spatial configuration of structures in multiobject segmentation. It is defined as follows.…”
Section: Spatial Configuration Priormentioning
confidence: 99%
See 3 more Smart Citations